Influence of Nitrate and Nitrite on Thyroid Hormone Responsive and Stress-Associated Gene Expression in Cultured Rana catesbeiana Tadpole Tail Fin Tissue - Hinther, Ashley; Edwards, Thea M.; Guillette, Louis J.; Helbing, Caren (Frontiers in Genetics, 2012)
Nitrate and nitrite are common aqueous pollutants that are known to disrupt the thyroid axis. In amphibians, thyroid hormone (TH)-dependent metamorphosis is affected, although whether the effect is acceleration or deceleration of this developmental process varies from study to study. One mechanism of action of these nitrogenous compounds is through alteration of TH synthesis. However, direct target tissue effects on TH signalling are hypothesized. The present study uses the recently developed cultured tail fin biopsy (C-fin) assay to study possible direct tissue effects of nitrate and nitrite. Tail biopsies obtained from premetamorphic Rana catesbeiana tadpoles were exposed to 5 mg/L and 50 mg/L nitrate (NO3-N) and 0.5 mg/L and 5 mg/L nitrite (NO2-N) in the absence and presence of 10 nM T3. Thyroid hormone receptor β (TRβ) and Rana larval keratin type I (RLKI), both of which are thyroid hormone responsive gene transcripts, were measured using quantitative real time polymerase chain reaction. To assess cellular stress which could affect TH signalling and metamorphosis, heat shock protein 30 (HSP30) and catalase (CAT) transcript levels were also measured. We found that nitrate and nitrite did not significantly change the level of any of the four transcripts tested. However, nitrate exposure significantly increased the heteroscedasticity in response of TRβ and RLKI transcripts to T3. Alteration in population variation in such a way could contribute to the previously observed alterations of metamorphosis in frog tadpoles, but may not represent a major mechanism of action.